Analysis of the Development of Qur’an–Hadith Learning in Improving the Quality of Islamic Religious Education in the Modern Era at Madrasah Tsanawiyah - Latifah Latifah; Sinta Masitha; Khairunnida Khairunnida; Hasni Noor (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study analyzes the development of Al-Qur'an Hadith learning in Islamic Junior High Schools (MTs) as an effort to improve the quality, relevance, and effectiveness of Islamic Religious Education in facing the challenges of the modern era. The purpose of this study is to describe the concept and implementation of Al-Qur'an Hadith learning development from the aspects of materials, methods, media, and evaluation. This study employed a library research method, collecting data from books, journals, and relevant academic literature. The data were analyzed descriptively and qualitatively to obtain a comprehensive overview of the development of Al-Qur'an and Hadith learning in MTs. The results indicate that learning development needs to be carried out holistically through the integration of cognitive, affective, and psychomotor domains, as well as the application of contextual and thematic approaches so that students are able to understand and practice the values ​​of the Al-Qur'an and Hadith in everyday life. The use of digital media, interactive methods, and authentic assessment are essential components in developing learning that aligns with technological developments and student characteristics. This research also emphasizes the importance of teacher innovation in utilizing technology such as multimedia applications, cooperative learning models, and digital evaluation platforms to improve student motivation and learning outcomes. Overall, developing Qur'an and Hadith learning in Islamic Junior High Schools (MTs) is an urgent need to shape students to be knowledgeable, have noble character, and adapt to the complexities of modern education.